The Influence of Principal Leadership and Teacher Work Motivation On Teacher Performance - Silaen, Maria; Purba, Sukarman; Hajar, Ibnu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The objectives of this study are (1) to determine the influence of principal leadership on teacher performance; (2) to determine the influence of teacher work motivation on teacher performance; and (3) to determine the influence between principal leadership and teacher work motivation on teacher performance at SMA Negeri 4 Medan. This study is a type of quantitative descriptive research. The sample in this study was 30 people. The data collection technique was through a questionnaire. The data analysis technique used was the multiple linear regression method. The results of this study indicate that: (1) that leadership has a positive and significant influence on teacher performance, with a calculated t value of 2.282> t table 2.048 and a significance value of 0.002 <0.005. (2) . Furthermore, work motivation is also proven to have a positive and significant influence on teacher performance, with a calculated t value of 4.483> t table 2.048 and a significance value of 0.000 <0.005. (3) Simultaneous leadership and work motivation together provide a positive and significant influence on teacher performance, as indicated by the calculated F value of 22.885 > F table 3.354 with a significance of 0.000 < 0.005. The conclusion is that the principal's leadership and teacher work motivation have a positive influence on teacher performance at SMA Negeri 4 Medan. The findings in this study are that many teachers are still not motivated enough in carrying out their duties as educators.